Addressing Enforced Disappearances in Criminal Law: Legal and Procedural Perspectives from Ukraine and Bosnia and Hercegovina - Ablamskyii, Serhii; Hloviuk, Iryna; Kazić Çakar, Ena; Zinkovskyy, Igor (PRAWO i WIĘŹ, 2025)
The notion of enforced disappearance has been a serious violation of human right as the right to life and to liberty. The increase in the case of enforced disappearance in the society today and those of Ukraine and Bosnia and Herzegovina is in the increase and this crime is so rampant in these society. The objective and purpose of this paper is to show the extent that the crime of enforced disappearance has affected the population of Ukraine and Bosnia and Herzegovina, and how this crime has affected the criminal proceedings in most cases. In answering the above objective, it will be essential for us to look at an analytical research method, together with normative and comparative legal methods, in observing how the State of Ukraine and Bosnia and Herzegovina has been able is prosecuting this offence in consonant with the criminal texts and other legal instruments that these states has enacted in handling the said crime in question. Based on that, one can say that through the State of Ukraine and Bosnia and Herzegovina has the relevant laws criminalizing the above crime, this crime commission continue to be on the increase as the devastating effects are disastrous and the loss of human life enormous. From this set, one is pose to find out what can really be done in ensuring that the population of Ukraine and those of Bosnia and Herzegovina should be safe and not deprived of their fundamental right to life, it therefore becomes the responsibility of those in charge of criminal justice should properly enhance the criminal process so that those responsible for these crimes should be prosecuted accordingly.